2011
DOI: 10.1271/bbb.100710
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavone Equol Perpetuates Dextran Sulfate Sodium-Induced Acute Colitis in Mice

Abstract: The effects of the soy isoflavones, genistein, daidzein and equol, on experimental colitis were examined. Equol severely perpetrated dextran sulfate sodium (DSS)-induced colitis as evaluated by the weight loss. Production of the anti-inflammatory cytokine, IL-10, from T cells was decreased in the equol-treated mice. The results show that the soy isoflavone, equol, played an important role in the inflammatory response in the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Similar to EGCG, green tea polyphenols at doses <0.5 % inhibited DSS-induced colitis, whereas doses of 0.5-1 % fortified colitis symptoms and mortality [59][60][61]. Another example is represented by genistein that a dose of 20 mg/kg reduced survival relative to the non-treated DSS-CTL group whereas lower concentrations (2 and 10 mg/kg) were more beneficial [62]. Evaluation of the preventive and therapeutic effects of DAPP showed a significant improvement of the DSS-induced clinical manifestations, as evidenced by the alleviation of body weight loss, diarrhoea and faecal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to EGCG, green tea polyphenols at doses <0.5 % inhibited DSS-induced colitis, whereas doses of 0.5-1 % fortified colitis symptoms and mortality [59][60][61]. Another example is represented by genistein that a dose of 20 mg/kg reduced survival relative to the non-treated DSS-CTL group whereas lower concentrations (2 and 10 mg/kg) were more beneficial [62]. Evaluation of the preventive and therapeutic effects of DAPP showed a significant improvement of the DSS-induced clinical manifestations, as evidenced by the alleviation of body weight loss, diarrhoea and faecal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that the main bioactive compounds in soy sauce, including genistein and daidzein, effectively reduce the levels of TNF-a, an important inflammatory mediator, elevated by IBD in experimental rodent models. [46][47][48] Genistein also fails to decrease T-cell proliferation and reduces the production of IL-1b and IL-6 in lipopolysaccharide (LPS)-treated mice. 49 Sesamin and sesamolin have been shown to inhibit TNF-a, IL-1b, and IL-6 activity in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol inhibited CIA progression by reducing the production of pro-inflammatory cytokines, the expression of MMPs, and oxidative stress. Also, as explained by Morimoto et al [83], natural soy isoflavones such as genistein and daidzein present as inactive β-glycosides and are converted in vivo to the active bioavailable aglycone form by enterobacteria. Isoflavones exist primarily as glucoside forms and rarely as aglycone forms.…”
Section: Flavonoids and Related Compoundsmentioning
confidence: 99%
“…Chao et al [80] reported that honokiol at 10 µg/ml inhibited LPS-induced TNF-α secretion in macrophages without affecting the activity of the TNF-α converting enzyme. A recently published note [83] argues that soy isoflavones perpetuate DSS-induced ulcerative colitis in mice instead of ameliorating it. With the aid of confocal microscope analysis, the authors observed that honokiol inhibited phosphorylation and membrane translocation of protein kinase (PK)C-α as well as NF-κB activation.…”
Section: Flavonoids and Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation